The occurrence of Dermacentor reticulatus tick (Acari: Amblyommidae) in north-east Slovenia: one more evidence for its increased distribution range - Gračner, Maja (Acta entomologica slovenica (Ljubljana), 2017)
The occurrence of Dermacentor reticulatus on the territory of Slovenia was not described before. By extensive 3.5 year sampling period, we obtained sufficient data allowing for the first time to clearly define the distribution rate and seasonal activity of adult D. reticulatus in this part of Europe, north-east Slovenia. A study was conducted from November 2003 to May 2007 to evaluate the comprehensive view of the annual seasonality of questing adult D. reticulatus. Ticks monitoring was conducted in three different localities%habitats: a) Muriša - wet meadows near oxbow lake of the river Mura; b) Murska šuma - swampy forest area between the confluence of the river Mura and Ledava, which is occasionally flooded; and c) Dolinski pašnik - meadows with old oak trees, forest edge and shrub communities. In total, 2511 ticks were collected by flagging. There were exclusively adults with female-biased sex ratio throughout the years in all sampling localities, namely for Muriša 59.5% (1287 of 2164), Murska šuma 62.7% (203 of 324) and Dolinski pašnik 60.8% (14 of 23). Most of the ticks (89.2%) were collected when the mean daily temperatures were ranging from 0 to 14.9%C. The highest activity of D. reticulatus were noted in the spring, culminating in February-April/May, peaking in average in March and with considerably lower rate (3-8-times) in the second activity peak in autumn, culminating in the end of August/September-November. The greatest number of adults in autumn was collected in October or November. Dermacentor reticulatus was not active during the summer months. The highest quantity of ticks was recorded in meadows near oxbow lake of the river Mura where was caught 6.6-times more ticks than in swampy forest area Murska šuma, which was occasionally flooded after huge rainfall and even 94-times more than in Dolinski pašnik. The confirmed occurrence of D. reticulatus in north-eastern Slovenia provided evidence that this species has extended its range. Our findings point to an enlargement of Pannonian distribution area of the species. This study indicates that D. reticulatus can be ranked as a typical element of the fauna in north-eastern Slovenia.
Keywords: Acari; Amblyommidae; Dermacentor reticulatus; distribution; klopi; paraziti; prevalence; razširjenost; seasonality; severni ornamentirani klopi; sezonska aktivnost; Slovenia; Slovenija; ticks; zoology